Serological Evidence of Henipavirus among Horses and Pigs in Zaria and Environs in Kaduna State, Nigeria. (25th November 2015) - Olufemi, Olaolu T.; Umoh, Jarlath U.; Dzikwi, Asabe A.; Olufemi, Yemisi O.
Abstract : Henipavirus is an emerging, zoonotic, and lethal RNA virus comprising Hendra virus ( HeV ) and Nipah virus ( NiV ), to which fruit bats are reservoir. Husbandry practices in Nigeria allow close contact between bat reservoir and animals susceptible to Henipavirus . This cross-sectional survey investigated antibodies reactive to Henipavirus sG antigen and associated risk factors in horses and pigs in Zaria, Nigeria. Using convenience sampling, 510 sera from horses (n = 200 ) and pigs (n = 310 ) were screened by an indirect Henipavirus enzyme-linked immunosorbent assay (ELISA) (CSIRO, Australia). Structured questionnaires were employed with questions on the demographics and management of the animals. Data were analysed using SPSS-17. 5. Seroprevalence was higher for horses managed intensively (21.1%); used for sports (25.5%); watered with pipe borne water (17.9%); fed commercial feed (22.3%); and fed in the pen (17.6%). Seroprevalence was higher for pigs managed intensively (58.1%); imported (69.5%); watered with pipe-borne water (31.3%); fed commercial feed (57.4%); fed in the pen (23.4%), and fed with feed prestored in a feed house (49.5%). Horses <5 years and pigs <6 months had higher seroprevalences of 18.1% and 21.3%, while the female horses and pigs had seroprevalences of 19.8% and 22.8%, respectively. Exotic horses and pigs revealed 25.5% and 55% and horses in Igabi and pigs in Giwa revealed 24.7% and 70.2% seroprevalence, respectively (P < 0.05 ). There is a suggestive evidence of Henipavirus in horses and pigs in Zaria, Nigeria, with a huge public health implication. Local and exotic pigs and horses, pigs in Zaria and Sabon-Gari, and horses in Zaria, Sabon-Gari, and Kaduna North are associated with the seroprevalence of henipaviruses.